SOSIALISASI DAN PENDAMPINGAN PEMBAYARAN FIDYAH BAGI IBU HAMIL DAN MENYUSUI DI DUSUN BULU I DESA BULU KECAMATAN SAMBIT PONOROGO - Musarofah, Siti (Institut Agama Islam Riyadlotul Mujahidin, 2024)
This Community Service aims to: teach procedures for paying fidyah to pregnant and breastfeeding mothers in Dusun Bulu 1, Bulu Village, Sambit District, Ponorogo as accordance with Islamic law, accompany the implementation of fidyah payments by pregnant and breastfeeding mothers in Dusun Bulu 1, Bulu Village, District Sambit Ponorogo who does not fast during Ramadan. The Community Service implementation method includes: preparation stage, the Community Service implementation stage which includes socialization and fidyah payments, and evaluation stage. The results achieved from this Community Service activity include: preparation stage, Community Service implementation stage which includes socialization and fidyah payments, and evaluation stage. The results achieved from this Community Service activity include: (1) increased understanding of the procedures for paying fidyah for pregnant and breastfeeding mothers. (2) Pregnant and breastfeeding women in Bulu I Hamlet, Bulu Village who do not fast during Ramadan have the awareness to pay fidyah. (3) Sustainability of the Community Service program in the form of the existence of a payment and fidyah distribution committee for pregnant and breastfeeding mothers.